PEMBINAAN JIWA WIRAUSAHA MELALUI PROYEK KULINER JAJANAN LOKAL PADA MADRASAH ALIYAH MUHAMMADIYAH SANIANG BAKAR - Muhammad Fadli; Ardi Satrial; Nurhayati (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This activity aims to improve students’ skills in processing local snacks on the theme of entrepreneurship. This service activity was carried out using partisipatory action research (PAR). Researchers are directly involved in facilitating students in local snacks culinary entrepreneurship project activities. The Pancasila and Rahmatan lil 'Alamin Profile Project activities are carried out collaboratively in the school environment between students, who teachers and researchers accompany. In this project, there are also research-related activities, with direct observation and assessment of projects produced by students. The results of this service found that students’ skills in making local culinary snacks were at the level of starting to develop in the collaborative aspect and were growing in the creative aspect. This means that entrepreneurship project activities have a wedge with students’ character, fostering cooperation and imaginative characters.